Low extracellular vesicle concentrations predict survival in patients with heart failure - Schöler, David; Loosen, Sven H.; Wirtz, Theresa H.; Brozat, Jonathan F.; dos Santos Ferreira Grani, Lauredana A.; Luedde, Tom; Heinrichs, Lisa; Frank, Derk; Koch, Alexander; Roderburg, Christoph; Spehlmann, Martina E. (Frontiers in Cardiovascular Medicine, 2023)
Background Heart disease is of worldwide importance due to high morbidity and mortality. Extracellular vesicle (EV) concentration and size represent novel diagnostic and prognostic biomarkers, e.g. in patients with liver cancer, but data on their prognostic relevance in heart disease are lacking. Here, we investigated the role of EV concentration, size and zeta potential in patients with heart disease. Methods Vesicle size distribution, concentration and zeta potential were measured by nanoparticle tracking analysis (NTA) in 28 intensive care unit (ICU) and 20 standard care (SC) patients and 20 healthy controls. Results Patients with any disease had a lower zeta potential compared to the healthy controls. Vesicle size (X50) was significantly higher in ICU patients (245 nm) with heart disease as compared to those patients with heart disease receiving standard care (195 nm), or healthy controls (215 nm) (p = 0.001). Notably, EV concentration was lower in ICU patients with heart disease (4.68 × 1010 particles/ml) compared to SC patients with heart disease (7,62 × 1010 particles/ml) and healthy controls (1.50 × 1011 particles/ml) (p = 0.002). Extracellular vesicle concentration is prognostic for overall survival in patients with heart disease. Overall survival is significantly reduced when the vesicle concentration is below 5.55 × 1010 particles/ml. Median overall survival was only 140 days in patients with vesicle concentrations below 5.55 × 1010 particles/ml compared to 211 days in patients with vesicle concentrations above 5.55 × 1010 particles/ml (p = 0.032). Summary Concentration of EVs is a novel prognostic marker in ICU and SC patients with heart disease.